Application of PCR and DNA probes in the characterisation of trypanosomes in the blood of cattle in farms in Morogoro, Tanzania - Mugittu, K.N.; Silayo, R.S.; Majiwa, Phelix A.O.; Kimbita, E.K.; Mutayoba, B.M.; MaSelle, R. (Elsevier, 2001)
Polymerase chain reaction (PCR) and deoxyribonucleic acid (DNA) probes were used to characterize trypanosomes from cattle in Morogoro region of Tanzania. Blood samples collected from 390 beef and dairy cattle in selected farms in Morogoro region were examined for presence of trypanosomes using the buffy coat technique (BSs). Fifty-two animals were found infected: 40 with Trypanosoma congolense, 10 with T. vivax and two with both T. congolense and T. vivax. DNA extracted from all the parasitologically positive and 62 randomly selected parasitologically negative samples were subjected to PCR amplification using primers specific for different trypanosome species. Using a set of seven specific-pairs of primers on the parasitologically positive samples, we detected only T. congolense, either the Savannah- or the Kilifi-type, as single or mixed infections. With the PCR, trypanosome DNA could be detected in 27 (43 percent) out of 62 samples that were parasitologically negative. DNA hybridization using probes specific for Savannah- or Kilifi-types T. congolense, or T. vivax, confirmed the presence of these parasites in cattle kept on some farms in Morogoro region of Tanzania. From these studies, it is clear that there is a need to undertake molecular epidemiological studies to determine the distribution of trypanosome species and subspecies, and to assess the economic impact of these parasites in the productivity of livestock in Tanzania. In particular, it would be desirable to verify the assumed association between the different presentations of trypanosomosis on one hand and genotypes of T. congolense on the other.